2013
DOI: 10.1371/journal.pone.0073813
|View full text |Cite
|
Sign up to set email alerts
|

Time- and Task-Dependent Non-Neural Effects of Real and Sham TMS

Abstract: Transcranial magnetic stimulation (TMS) is widely used in experimental brain research to manipulate brain activity in humans. Next to the intended neural effects, every TMS pulse produces a distinct clicking sound and sensation on the head which can also influence task performance. This necessitates careful consideration of control conditions in order to ensure that behavioral effects of interest can be attributed to the neural consequences of TMS and not to non-neural effects of a TMS pulse. Surprisingly, eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 18 publications
(22 reference statements)
6
37
1
Order By: Relevance
“…Audible ‘clicks’ from a TMS machine can have differential attentional cuing effects when presented at different time points [44], and thus have the potential to influence behavior differently early versus late during a memory delay. Because sham TMS has no neural effects, we collected a total of 320 sham trials (160 per pulse timing) for each participant to investigate possible effects of pulse timing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Audible ‘clicks’ from a TMS machine can have differential attentional cuing effects when presented at different time points [44], and thus have the potential to influence behavior differently early versus late during a memory delay. Because sham TMS has no neural effects, we collected a total of 320 sham trials (160 per pulse timing) for each participant to investigate possible effects of pulse timing.…”
Section: Resultsmentioning
confidence: 99%
“…A TMS coil (real or sham) was placed over either the left or the right dorsal part of early visual cortex (V1/V2). Sham TMS was used to control for attentional biasing effects that can arise from “clicking” sounds at different points in time [44]. For half of our participants, a single session consisted of 4 blocks of 80 working memory trials per block, of which three blocks involved triple-pulse TMS stimulation at 10 Hz, and one block involved triple-pulse sham stimulation at 10 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…This was highly beneficial as this meant that the comparisons of our four experimental conditions involved the exact same TMS stimulation. This optimal control could have not been achieved by using either sham or vertex stimulation, alternative procedures commonly used in TMS research [8, 19, 40] to mimic the TMS coil click but that do not control for all TMS-associated peripheral sensations. Moreover, given that TMS was close to the inter-hemispheric fissure, the noise it produced could not be responsible for the observed effects, as it would not have induced differential effects for the target and distractor that were presented in separate hemifields.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, magnetic stimulations delivered with the coil in various tilted positions demonstrated that none of the sham positions tested were ideal sham due to the possibility of slight cortical activation as measured by the integrated voltage recorded with intracranial electrodes (Lisanby et al, 2001) and due to a lesser scalp sensation (Loo et al, 2000). Furthermore, the 90° coil tilting and the shield equipped coils that reduce the effective magnetic field by approximately 80% fail to evoke somatosensory sensation perceived with the active TMS (Duecker et al, 2013). To reproduce click sound and somatosensory sensations, new sham coils have been manufactured, looking alike active coils but equipped with a magnetic shield resulting in a delivered magnetic field of only 10% compared to active coils (Sommer et al, 2006).…”
Section: Therapeutic Procedures In Dystoniamentioning
confidence: 99%